2010
DOI: 10.1007/s12012-010-9069-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lipophilic Bile Acids in the Development of Cirrhotic Cardiomyopathy

Abstract: Marked hemodynamic changes occur in humans and experimental animals with cirrhotic liver disease. In the heart, basal contractility, responsiveness to beta-adrenoceptor activation, and excitation-contraction coupling (ECC) are negatively affected in models of cirrhosis and portal hypertension with portosystemic shunting (PVS), and comprise what has been called cirrhotic cardiomyopathy. These effects are accompanied by elevated circulating levels of bile acids. We investigated whether elevated bile acids act as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
1
18
0
1
Order By: Relevance
“…Zavecs and Battarbee have shown that acute exposure of cardiac muscle to cholic acid mimics several characteristics of cardiac dysfunction observed in cirrhotic rat models including depressed β‐adrenoceptor‐mediated inotropism and decreased depolarization‐dependent calcium entry. Furthermore, replacing lipophilic BAs with UDCA reduces cardiac impairment . By obtaining similar results in cirrhotic and noncirrhotic portal vein stenosis models, their results suggest that bile acids themselves are significant factors in the genesis of cirrhotic cardiomyopathy.…”
Section: Bile Acids and Their Relationship With Cirrhotic Cardiomyopathymentioning
confidence: 73%
“…Zavecs and Battarbee have shown that acute exposure of cardiac muscle to cholic acid mimics several characteristics of cardiac dysfunction observed in cirrhotic rat models including depressed β‐adrenoceptor‐mediated inotropism and decreased depolarization‐dependent calcium entry. Furthermore, replacing lipophilic BAs with UDCA reduces cardiac impairment . By obtaining similar results in cirrhotic and noncirrhotic portal vein stenosis models, their results suggest that bile acids themselves are significant factors in the genesis of cirrhotic cardiomyopathy.…”
Section: Bile Acids and Their Relationship With Cirrhotic Cardiomyopathymentioning
confidence: 73%
“…These human experiments, which were faithfully reproduced in isolated adult mouse cardiomyocytes, further strengthen the long-held notion that high levels of circulating bile acids adversely affect myocardial cell biology. More importantly, these studies add clinical relevance to the animal studies which speculated a role for bile acids in the pathophysiology of cardiac dysfunction in cirrhosis,13 14 termed cirrhotic cardiomyopathy,15 16 which has a prevalence of ∼50% according to some studies 17 18. Electrocardiographic abnormalities, more specifically prolonged QT interval is a key derangement of cirrhotic cardiomyopathy and is known to cause sudden death in adults 19 20 and increases mortality risk in children21 with liver failure.…”
mentioning
confidence: 85%
“…Elevated serum bile acids have long been speculated to cause cirrhotic cardiomyopathy . In fact, bile was first observed to mediate cardiotoxicity almost a century ago .…”
mentioning
confidence: 91%